In vitro evaluation of antimicrobial and anti-biofilm properties of antiseptics against multidrug resistant clinical Escherichia coli strains, isolated from combat wounds - O. Nazarchuk; T. Denysko; D. Dmytriiev; N. Chornopyshchuk; O. Hruzevskyi; V. Burkot; H. Nazarchuk; K. Ksenchyna (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
The necessity for the investigation of novel approaches and strategies for the treatment of multidrug-resistant E. coli related infections becomes more and more essential. Purpose - to investigate and compare the level of antimicrobial and anti-biofilm activity of antiseptic preparations against MDR clinical isolates of E. coli. Materials and methods. In vitro effectiveness of modern antiseptics; octenidine 0.1% (OCT), polyhexanide 0.1% (PHMB), chlorhexidine 0.5% (CHG), miramistin 0.01% (MRM), decamethoxine 0.1% 0.02% (DCM), povidone-iodine 10% (PVP-I), was determined against forty-six polyresistant clinical strains of E. coli. MIC, MBC were found by standard methods, the value of which was interpreted as a bacteriostatic and bactericidal index of antiseptic activity (BS IAA and BC IAA). The effect of antiseptics on the immature biofilm was modelled using the Christensen test. Results. MIC and MBC values were the lowest in DCM and OCT. The highest values of the antiseptic activity index (IAA>4) were determined for the antiseptics PHMB 0.1%, OCT 0.1% and DCM 0.1%. It was found that the feasibility of using MRM at a concentration of 0.01% is questionable as the BS IAA is above the threshold value, while the BC IAA is not. The effectiveness of PVP-I 1% against MDR E. coli was found insufficient. Sub-bacteriostatic concentrations of DCM, CHG, and PHMB reliably inhibited the formation of E. coli biofilms within 24 hours. MRM and PVP-I in sub-bacteriostatic concentrations stimulated biofilm formation. Conclusions. Based on the analysis of all conducted studies, 0.1% and 0.02% DCM, 0.05% CHG, 0.1% OCT, 0.1% PHMB, 10% and 2% PVP-I are the most active against MDR clinical isolates of E. coli. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.